Reading Psalm 23 in African context - Adamo, David T. (Verbum et Ecclesia, 2018)
The book of Psalms is the best known, most discussed and most cited book of the Old Testament. Psalm 23 especially is the most loved book of the Psalms. That must have been the reason why it was named ‘an American icon’ and the ‘nightingale of the Psalms’. Two major ways of reading this Psalm are: as a shepherd to a sheep and as God to a human. The author of this article reads Psalms 23 Africentrically, that is, as God to a human. This means that Psalms 23 is read for the purpose of protection, provision, healing and success in all aspects of life, which are the main concerns of African people. It means reading Psalm 23 existentially with African life interest. Intradisciplinary and/or interdisciplinary implications: This article is concerned with biblical studies, African Traditional Religion and culture and African Biblical Hermeneutics. It seeks to challenge the traditional Eurocentric approaches for its methodological approaches that do not make biblical studies adequately relevant to African Christianity. The book of Psalms is used as a perfect example of how it can be interpreted relevantly in Africa. Further implication is that there will be reduction of the Bible and Christianity looking like a foreign book and religion.
free